Patterns and trends of potentially inappropriate high-density lipoprotein cholesterol testing in Australian adults at high risk of cardiovascular disease from 2008 to 2014: analysis of linked individual patient data from the Australian Medicare Benefits Schedule and Pharmaceutical Benefits Scheme. Issue 3 (8th March 2018) - Hajati, Farshid; Atlantis, Evan; Bell, Katy J L; Girosi, Federico
Abstract : Objectives: We examine the extent to which the adult Australian population on lipid-lowering medications receives the level of high-density lipoprotein cholesterol (HDL-C) testing recommended by national guidelines. Data: We analysed records from 7 years (2008–2014) of the 10% publicly available sample of deidentified, individual level, linked Medicare Benefits Schedule (MBS) and Pharmaceutical Benefits Scheme (PBS) electronic databases of Australia. Methods: The PBS data were used to identify individuals on stable prescriptions of lipid-lowering treatment. The MBS data were used to estimate the annual frequency of HDL-C testing. We developed a methodology to address the issue of 'episode coning' in the MBS data, which causes an undercounting of pathology tests. We used a published figure on the proportion of unreported HDL-C tests to correct for the undercounting and estimate the probability that an HDL-C test was performed. We judged appropriateness of testing frequency by comparing the HDL-C testing rate to guidelines' recommendations of annual testing for people at high risk for cardiovascular disease. Results: We estimated that approximately 49% of the population on stable lipid-lowering treatment did not receive any HDL-C test in a given year. We also found that approximately 19% of the same population received two or more HDL-C tests within the year. These levels of underutilisation and overutilisation have been changing at an average rate of 2% and −4% a year, respectively, since 2009. The yearly expenditure associated with test overutilisation was approximately A4.3 million during the study period, while the cost averted because of test underutilisation was approximately A11.3 million a year. Conclusions: We found that approximately half of Australians on stable lipid-lowering treatment may be having fewer HDL-C testing than recommended by national guidelines, while nearly one-fifth are having more tests than recommended.